MACC1 and MET as markers associated with progression and metastasis in cutaneous melanoma - Zhou, Yan; Rasner, Cody J.; Giubellino, Alessio (Frontiers in Oncology, 2023)
Cutaneous melanoma is the most common lethal malignancy among skin cancers and has a high propensity for metastasis. Understanding the mechanisms governing tumorigenesis, progression and metastasis as well as identifying biomarkers guiding risk stratification and management of the disease is essential. MACC1 has been found to play key roles in cancer cell migration, invasion, epithelial-to-mesenchymal transition, and metastasis in various types of cancer, through activation of MET signaling. In this study, we examined the extent of MACC1 and MET protein expression by immunohistochemical staining in a tissue microarray constructed from twenty-three melanomas and ten melanocytic nevi. We observed significantly higher levels of MACC1 expression on average in metastatic melanomas, comparing to primary melanomas and nevi. MET expression in metastatic melanomas was also significantly higher than in nevi. MACC1 expression does not appear to correlate with MET expression in nevi and primary melanomas. However, this correlation appears stronger in metastatic melanomas, where seven (78%) of nine cases show intermediate to high expression of both MACC1 and MET. The expressions of MACC1 and MET do not show significant differences based on other clinicopathologic factors including patient age, gender, histologic subtypes, depth of invasion, and staging. Our study suggests that high expression of MACC1 or both MACC1 and MET is associated with metastasis of cutaneous melanoma.